Measuring the effects of the COVID-19 pandemic on Diné and White Mountain Apache school personnel, families, and students: protocol for a prospective longitudinal cohort study - Joshuaa D. Allison-Burbank; Allison Ingalls; Paul Rebman; Rachel Chambers; Renae Begay; Ryan Grass; Alicia Tsosie; Shannon Archuleta; Allison Barlow; Francene Larzelere; Laura Hammitt; Lauren Tingey; et al. (BMC, 2022)
Abstract Background This paper describes the protocol for a longitudinal cohort study, "Project SafeSchools" (PSS), which focuses on measuring the effects of COVID-19 and the return to in-person learning on Diné (Navajo) and White Mountain Apache (Apache) youth, parents, and educators. The early surges of the COVID-19 pandemic led to the closure of most reservation and border town schools serving Diné and Apache communities. This study aims to: (1) understand the barriers and facilitators to school re-opening and in-person school attendance from the perspective of multiple stakeholders in Diné and Apache communities; and (2) evaluate the educational, social, emotional, physical, and mental health impacts of returning to in-person learning for caregivers and youth ages 4-16 who reside or work on the Diné Nation and the White Mountain Apache Tribal lands. Methods We aim to recruit up to N = 200 primary caregivers of Diné and Apache youth ages 4-16 and up to N = 120 school personnel. In addition, up to n = 120 of these primary caregivers and their children, ages 11-16, will be selected to participate in qualitative interviews to learn more about the effects of the pandemic on their health and wellbeing. Data from caregiver and school personnel participants will be collected in three waves via self-report surveys that measure COVID-19 related behaviors and attitudes, mental health, educational attitudes, and cultural practices and beliefs for both themselves and their child (caregiver participants only). We hypothesize that an individual's engagement with a variety of cultural activities during school closures and as school re-opened will have a protective effect on adult and youth mental health as they return to in-person learning. Discussion The results of this study will inform the development or implementation of preventative interventions that may help Diné and Apache youth and their families recover from the negative impact of the COVID-19 pandemic, and positively impact their health and wellness.